Perceived public alarm and comprehension of risk communication messages about Lassa fever in Nigeria: a gauge of the risk communication model - Ben-Enukora, Charity Amaka; Oyero, Olusola; Okorie, Nelson; Ejem, Agwu Agwu; Omowale, Adelabu Toafeek (Frontiers in Communication, 2023)
This study examined the influence of perceived panic (if any) on respondents’ comprehension of risk communication messages about Lassa fever vector, transmission routes, risk factors, and the preventive measures. The risk communication model (mental noise hypothesis) was used as the benchmark for measuring respondents’ perceptions in the most endemic states in Nigeria. The study adopted a quantitative approach, using the survey method. Data for this study was collected from 653 respondents through a structured questionnaire. Respondents were selected by means of multi-stage sampling technique. Frequency tables were used to profile the respondents’ characteristics and key variables while regression coefficients were used to draw inferences. We found a high level of perceived panic among the respondents but maximum attention was paid to risk communication messages in the midst of high level of anxiety. The knowledge of Lassa fever vector, transmission routes, high-risk factors and preventive measures was adequate irrespective of the high-level of perceived panic. Therefore, we conclude that maximum attention to risk communication messages in the midst of high level of anxiety could lead to increase in knowledge of Lassa fever among the audience members. However, the influence of the perceived panic on the knowledge of Lassa fever was statistically significant in Ebonyi and Ondo at r2=.040 and .076, at p˂0.05 but not in Edo state at r2=.010, at p > 0.05.